In-situ synthesised interlayer enhances bonding strength in additively manufactured multi-material hybrid tooling. (August 2020) - Tan, Chaolin; Zhang, Xinyue; Dong, Dongdong; Attard, Bonnie; Wang, Di; Kuang, Min; Ma, Wenyou; Zhou, Kesong
Abstract: Interfacial bonding reliability is a critical issue of metallic multi-material components due to the tendency to delaminate arising from the difference in physical and chemical properties between materials. Here we propose a novel approach to enhance the interfacial bonding through the in-situ synthesis of an interlayer in additively manufactured multi-material hybrid tooling via laser powder bed fusion (LPBF). The effects of laser parameters on tuning the interlayer formation and resulting bonding strength are investigated. The interfacial microstructure evolution, the in-situ formation mechanism of the interlayer, and the interface bond mechanisms are investigated. Intense Marangoni convection and inter-diffusion between two materials in interfacial melt pools, along with Cr redistribution segregation, facilitate the in-situ formation of a Cr-rich interlayer during LPBF process. The in-situ phase transformation behaviour in the interlayer is explained through the Schaeffler-Delong diagram. Mechanical tests, including flexural, tensile and nano-hardness tests, reveal that a strengthened/hardened interface (stronger than parent material) is obtained. The underlying interfacial bonding mechanism of the multi-materials is discussed in terms of the in-situ formed interlayer, Cr segregation and elemental diffusion, in-situ austenite formation together with intrinsic characteristics of the LPBF process. It is found that the in-situ formed interlayer serves to alleviate the interfacial mismatch with Cr-segregation leading to strengthening in the interface, while in-situ austenite formation counteracts residual tensile stress in the melt pool. Hybrid tooling developed in this way integrates complex geometry, improved productivity and high bonding strength. Graphical abstract: Image 1 Highlights: Laser parameter tunes in-situ formation of interlayer during LPBF process. In-situ formed interlayer enhances bonding strength of hybrid tooling. Interfacial bonding mechanism is investigated in multi-aspects. Hybrid manufacturing improves productivity and functionality.